PENDIDIKAN SEJARAH, SEBUAH TINJUAN METODOLOGI - Dita Hendriani (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This paper presents conceptual description on historical education  in the methods of historical discovery using library analyses.  The analyses indicate that (1) historical events can be described through two empirical facts: written and oral.  Conventional history accostomes only written facts;  in addition, oral facts that tend to be accepted as the complimentary materials support the written facts delineating a cross-check process to achieve the truth,  (2)  historical narration shoulb be clear-cut from tales; tales are produced by non-historian mixing facts and arts that should not be based on historical data, rather the author’s imagination, (3) phylosophy history is much written by non-historican but experts on phylosophy, and (4) history with Indonesian perspectives is significant to explore, hiwever much of the histiry is considered military oriented.